The effects of variety selection on the yield and productivity of sweetpotato-legume intercropping options in Malawi - Akinwale, Gbenga Moses; Chalie, Harvey; Mwenye, Obed J.; Chipungu, Felistus; Demo, Paul; Jogo, Wellington; Kreuze, Jan (Frontiers in Agronomy, 2025)
Crop diversification through integration of sweetpotato with legumes such as soybean presents a viable option for achieving food and nutrition security, income generation, soil fertility improvement, and adaptation to climate change in Malawi. However, knowledge regarding the choice of sweetpotato variety specifically adapted to intercropping systems remains a major obstacle to its optimization. The objective of the study was to evaluate three sweetpotato varieties under different intercropping systems. A field experiment was conducted using three Orange- fleshed Sweetpotato varieties (OFSP) with different vine length and growth habits (Kadyaubwerere -long vines, Royal choice-short vines, and Chipika - compact vines) under five spatial arrangements across three different agroecological zones during 2023–2024 cropping season. Five spatial arrangements including i) sole sweetpotato (Sole SP); ii) sole soybean (sole SB); iii) sweetpotato - soybean (1:1); iv) sweetpotato – soybean (2:1); and v) sweetpotato – soybean (2:2) were evaluated using a randomized complete block design in a split-plot arrangement with three replications. Agronomic data were subjected to analysis of variance using R programing. Land equivalent ratios (LERs) and absolute merit effect (AME) were also used to determine the productivity of the intercropping system. Variety architecture, locations, and intercropping systems significantly (P< 0.001) influenced the yields, and other traits of sweetpotato and soybean. Sweetpotato varieties responded differently under diverse spatial arrangements, indicating varietal effects on crop performance. LERs indicate significantly higher yield advantage in intercropping compared to sole cropping. LERs were greater than one (LER>1) in many of the intercrops, indicating higher productivity of intercropping over sole cropping. Across locations, Chipika and Royal choice sweetpotato varieties intercropped in ratios 1:1 and 2:1 gave the highest LERs as compared to Kadyaubwelere. The results suggest the combinations of Chipika-soybean in ratios 2:1 and 2:2 and Royal choice -soybean in ratios 1:1 and 2:2 for sweetpotato-intensification in Malawi due to the less competitiveness of the two varieties under the different intercropping arrangements.